Biodiversity of snails: a short review and commentary - Yap, Chee Kong; Cheng, Wan Hee (Nova Science Publishers, 2017)
This chapter presents a review and commentary of 45 reported publications in the literature on snail biodiversity. Of the 45 papers, it can be concluded that most papers (36 out of 45) fall into three categories: a) Regular checklist of snails is needed, b) New description of snail species would help in the species list documentation, and c) This information is important for future reference and for effective ecosystem management.